Pengaruh Asosiasi Merek, Loyalitas Merek, Brand Awarness, dan Citra Merek Terhadap Ekuitas Merek Produk Scarlett Whitening (Studi Kasus pada konsumen pembeli produk scarlett whitening pada mahasiswa prodi manajemen Angkatan 2019 Universitas Islam Malang) - Rista Sya’illatun Nandiroh; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of brand association, brand loyalty, brand awareness, brand image on brand equity of Scarlett products simultaneously and partially. Where to be able to achieve and maintain market competition, companies must pay attention to their brands by creating strong brand equity in the minds of customers. This study uses data analysis using multiple linear regression with SPSS version 29. The results of this study show that brand association has no positive and significant effect on brand equity, brand loyalty has no positive and significant effect on brand equity, brand awareness has a positive and significant effect on equity brand, brand image has a positive and significant effect on brand equity. brand association variables, brand loyalty, brand awareness, brand image have a positive and significant effect on brand equity. Keywords: brand equity,brand association,brand loyalty,brand awareness,brand image